(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article presents an analysis of information and sources on a scientific basis about the criminal legislation in force in our country and its practical application, as well as the role of international legal norms in these processes and the methods of its implementation in the legal structure of our country.